2015
DOI: 10.1088/0004-637x/805/2/167
|View full text |Cite
|
Sign up to set email alerts
|

PROPERTIES OF CHROMOSPHERIC EVAPORATION AND PLASMA DYNAMICS OF A SOLAR FLARE FROMIRISOBSERVATIONS

Abstract: Dynamics of hot chromospheric plasma of solar flares is a key to understanding of mechanisms of flare energy release and particle acceleration. A moderate M1.0 class flare of 12 June, 2014 (SOL2014-06-12T21:12) was simultaneously observed by NASA's Interface Region Imaging Spectrograph (IRIS), other spacecraft, and also by New Solar Telescope (NST) at the BBSO. This paper presents the first part of our investigation focused on analysis of the IRIS data. Our analysis of the IRIS data in different spectral lines… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
61
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 36 publications
11
61
0
Order By: Relevance
“…The two lines were redshifted during that time period, and remained redshifted even after the impulsive phase, gradually decreasing in magnitude over timescales exceeding 20 minutes at some positions. Similar trends in Si IV and other cool lines were reported by other authors in larger flares seen with IRIS, e.g., Sadykov et al (2015), Brannon et al (2015), Polito et al (2016).…”
Section: Introductionsupporting
confidence: 90%
“…The two lines were redshifted during that time period, and remained redshifted even after the impulsive phase, gradually decreasing in magnitude over timescales exceeding 20 minutes at some positions. Similar trends in Si IV and other cool lines were reported by other authors in larger flares seen with IRIS, e.g., Sadykov et al (2015), Brannon et al (2015), Polito et al (2016).…”
Section: Introductionsupporting
confidence: 90%
“…Recent results from the IRIS mission have also shown similar results but with strong down-flows seen in Fe XXI spatially coincident with the loop top -consistent with hot-retracting loops for example (Tian et al, 2014). Sadykov et al (2015) found evaporation flows in the Fe XXI ion in a flare. Polito et al (2015) found that after this blue-shifted plasma was observed, the Fe XXI intensity slowly moved from the footprints to the top of the flare loops.…”
Section: Evaporation In Flares -Is This Different In Eruptive and Nonsupporting
confidence: 57%
“…Perhaps the most significant challenge presented by these data is the persistent redshifts observed in Si IV and C II. Persistent redshifts have been observed with IRIS for a number of events and are not an idiosyncrasy of the data that we have analyzed (see Brannon et al 2015;Brosius & Daw 2015;Sadykov et al 2015;Polito et al 2016).…”
Section: Summary and Discussionmentioning
confidence: 68%